Simulation of tool safety system in conventional machining process using electro-pneumatic proximity sensor - Syaiful Syaiful; Roberth Marshall Ratlalan; Hermansyah; Anriyan; Haidir Jusman (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
In conventional machining processes, the means is a key component that directly influences the cutting results of the workpiece. However, the potential hazards posed by uncontrolled tool positioning in the work area often lead the risk of accidents and devise damage. This study aims to simulate a tool safety system on a lathe using an electro-pneumatic proximity sensor. The method used includes designing an automatic detection structure using a proximity sensor to monitor the safe distance between the tool, workpiece, machine spindle, and operator's hands. The system is controlled electro-pneumatically. Simulation results show that the system can accurately detect the presence of objects and automatically provide a machine stop signal when the tool is in a dangerous position. The implementation of this system has been proven to improve occupational safety during machining processes. Therefore, this design has the potential to be implemented as an additional protection system on conventional machines in the workplace